Work Stress in the Creative Industry: The Relationship Between Technostress, Burnout and Employee Innovation - Hermawati, Adya (PT. Anagata Sembagi Education, 2025)
The creative industry is highly dependent on digital technology, making workers vulnerable to technostress, which can lead to burnout and decreased innovation. This study aims to analyze the relationship between technostress, burnout, and employee innovation in the creative industry. This study uses a quantitative approach with an explanatory survey design, involving 300 respondents working in various creative sectors such as advertising, graphic design, digital marketing, animation, and film. Data were collected through a structured online questionnaire and analyzed using Structural Equation Modeling (SEM). The results show that technostress has a significant positive effect on burnout, while burnout has a negative impact on employee innovation. In addition, technostress also has a direct negative effect on employee innovation. Further mediation tests reveal that burnout partially mediates the relationship between technostress and employee innovation. These findings highlight the dual role of technostress as a direct and indirect determinant of employee innovation through burnout. Theoretically, this study contributes to the expansion of the Job Demands–Resources (JD-R) Model in the context of digital work. Practically, it suggests that organizations in the creative industry adopt strategies to reduce technostress and effectively manage burnout in order to maintain and enhance employees' innovative capacity.